2022
DOI: 10.1039/d2bm00558a
|View full text |Cite|
|
Sign up to set email alerts
|

Gram-selective antibacterial peptide hydrogels

Abstract: Human microbiome has fundamental roles in human health and disease. However, the widely used broad-spectrum antibiotics severely disrupt human-related microbial communities, eventually leading to resistant bacteria and posing a growing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 90 publications
3
23
0
Order By: Relevance
“…S. aureus without any treatment of the sample was considered as a negative control, and gentamycin sulfate was taken as a positive control. The activity against S. aureus is similar to the activity reported by Cao et al ., Hou et al ., Gahane et al ., and Bai et al …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…S. aureus without any treatment of the sample was considered as a negative control, and gentamycin sulfate was taken as a positive control. The activity against S. aureus is similar to the activity reported by Cao et al ., Hou et al ., Gahane et al ., and Bai et al …”
Section: Resultssupporting
confidence: 89%
“…S. aureus without any treatment of the sample was considered as a negative control, and gentamycin sulfate was taken as a positive control. The activity against S. aureus is similar to the activity reported by Cao et al, 49 Hou et al, 50 Gahane et al, 51 and Bai et al 52 Live/dead cell staining of S. aureus treated with gels was carried out with SYTO 9 and PI (Figure 4D). Bacteria were treated with gels for 12 h, and the staining solution was added followed by the incubation.…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…In addition, the N-terminus of the peptide motif FIIIKKK was modified to include hydrophobic groups naphthalene (Nap) and phloretic acid [3-(4-hydroxyphenyl) propionic acid] for the construction of the ACPs/AMPs IK1 and IK3, respectively, to promote peptide self-assembly (Figure a). The antibacterial activities of the IK1 and IK3 peptides and their efficacy as antibacterial hydrogel dressings have been thoroughly examined in our previously published work …”
Section: Resultsmentioning
confidence: 99%
“…We think that DN hydrogels , composed of polyvinyl alcohol (PVA) and ACPs may be particularly suitable to enhance the ACP hydrogels’ strength and toughness for biomedical use, as PVA is biocompatible and has little effect on the peptides’ characteristics such as assembly property and antitumor/antibacterial ability. , In this research, we have constructed ACP/PVA-based DN hydrogels for the direct treatment of melanoma. It was found that our previously developed AMPs, IK1 and IK3, which have excellent antibacterial properties, specifically target mouse melanoma cells B16-F10 while being nontoxic to healthy cells. IK1/PVA and IK3/PVA DN hydrogels were created.…”
Section: Introductionmentioning
confidence: 99%
“…Current strategies that are generally based on the cell membrane differences, such as membrane charge and sugar composition, have successfully achieved the antibacterial selectivity for Gram-positive or Gram-negative bacteria . Alternative strategies of selective antibacterial activity involve regulating the chemical structure of antibacterial agents, such as charges, hydrophobicity, and functions. For example, Tang’s group achieved the selectivity to Gram-positive bacteria by increasing the positive charges of amphiphiles . Banerjee’s group extended the alkyl chain to enhance the hydrophobicity of nanoparticles (NPs), and these amphiphiles displayed selectivity to Gram-negative bacteria .…”
mentioning
confidence: 99%